A Problem-Oriented Patient Management Scheme - Hearn, Catherine Rhys; Young, D. W. (Methods of Information in Medicine, 1975)
Inefficient patient care may occur not because of lack of medical skills or limitation of resources, but because of inconsistent or deficient application of current medical knowledge. Conventional recording of patient information in the traditional record makes it difficult to assess, for a group of patients with similar problems, the effectiveness of any particular management plan.The ›Problem-Oriented Patient Management Scheme‹ has been developed to overcome these two difficulties. In essence it is a method of organising management plans for handling of patient problems. As the plans are prespecified they should reflect current medical opinion, as they are written down they can be applied consistently, and as the data needed is itemized the resulting patient record should be analysable to assess the effectiveness of the particular management scheme.
Keywords: Problem-oriented DP; Interactive Computing; Logic Structure